The Effect of a Game-Based Run-and-Set Activity on Students’ Agility - Arya; Mita Erliana; Perdinanto; Akhmad Amirudin (STKIP Pasundan, 2026)
This study investigated the effectiveness of a game-based Run and Set activity in improving students’ agility in Physical Education, Sports, and Health (PJOK). A quasi-experimental one-group pretest–posttest design was employed. The participants were 31 eighth-grade students selected through purposive sampling. Agility was assessed using the shuttle run test administered before and after the intervention. Data analysis was conducted using the Shapiro–Wilk test for normality and a paired-samples t-test with SPSS. The results demonstrated a significant improvement in students’ agility, as indicated by higher posttest performance compared to pretest results. Statistical analysis confirmed a significant difference (p = 0.000 < 0.05), indicating that the Run and Set game had a statistically significant effect on agility development. These findings suggest that game-based learning strategies can serve as an effective pedagogical approach for enhancing physical fitness components, particularly agility, in school-based physical education contexts.